Analisis Kinerja Keuangan Dengan Metode Rasio Profitabilitas (ROA dan ROE) Pada Perusahaan Sektor Manufaktur di BEI Periode 2021-2024: Analysis of Financial Performance Using the Profitability Ratio (ROA and ROE) Method in Manufacturing Sector Companies on the IDX for the 2021-2024 Period - Suci Aulia Pratiwi; Henny Armaniah (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This research is based on the importance of evaluating financial performance to assess the effectiveness of resource management, particularly in the manufacturing sector, which plays a significant role in Indonesia’s national economy. Many manufacturing companies face profit fluctuations and low efficiency in utilizing assets and equity; therefore, a comprehensive profitability analysis is required. This study aims to analyze the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period using profitability ratios, namely Return on Assets (ROA) and Return on Equity (ROE). The research employs a descriptive quantitative method with a purposive sampling technique applied to 15 manufacturing companies. The data used are secondary data obtained from annual financial reports published by the IDX. The results show that ROA values range between 0.1%–30%, with an average of 8.9%, while ROE values range between 0.1%–152%, with an average of 18.7%. PT Unilever Indonesia Tbk (UNVR) recorded the highest ratios, while PT Chandra Asri Petrochemical Tbk (TPIA) and PT Barito Pacific Tbk (BRPT) had the lowest. These findings indicate the need for companies to enhance operational efficiency and optimize asset utilization to improve profitability.